Answer:
y=-4x+3
Step-by-step explanation:
as x=0
put in y= -4x+3
y= -4(0)+3
y=3
now put x=1 in y= -4x+3
y= -4(1)+3
y= -1
now put x=2 in y= -4x+3
y= -4(2)+3
y=-5
Answer:
x=2 and y=5
Step-by-step explanation:
Steps:
I will solve your system by substitution.
x=y−3;2x+y=9
Step: Solve x = y − 3 for x:
Step: Substitute y − 3 for x in 2x + y = 9:
2x+y=9
2(y−3)+y=9
3y−6=9(Simplify both sides of the equation)
3y−6+6=9+6(Add 6 to both sides)
3y=15
3y/3=15/3 (Divide both sides by 3)
y=5
Step: Substitute 5 for y in x = y − 3 :
x=y−3
x=5−3
x=2(Simplify both sides of the equation)
Answer:
x=2 and y=5
Answer:
![a^{3} \sqrt[]{a}](https://tex.z-dn.net/?f=a%5E%7B3%7D%20%5Csqrt%5B%5D%7Ba%7D)
Step-by-step explanation:
Answer:
Here is the solution...hope it helps:)